Adaptive flood governance in the Vietnamese Mekong Delta: A policy innovation of the North Vam Nao scheme, An Giang Province. Issue 108 (June 2020) - Tran, Thong Anh; Pittock, Jamie; Tran, Dung Duc
Highlights: The North Vam Nao scheme represents a hybrid governance paradigm. The scheme is characterised by the participatory and hierarchical approaches for its irrigation and flood management. Collaborative learning and integration of knowledge among stakeholders take place across vertical and horizontal linkages. The scheme fosters both 'integrative' and 'adaptive' components in its long-term water governance strategy. Abstract: Conventional state policies for intensive agricultural production in the Vietnamese Mekong Delta (VMD) prescribe the expansion of large-scale water engineering infrastructure. In the upper part of the VMD, compounding environmental challenges presented by climate change, hydropower development upstream, and localised development policies have added greater pressures to rural societies, demanding various governance approaches to deal with change. So far, considerable attention has been devoted to policy narratives of how the bureaucratic approach shapes flood management delta-wide, but little is known about the relevant shift towards adaptive governance at the local level. The analysis presented here is based on qualitative data gathered from fieldworks and desk reviews and argues that the North Vam Nao scheme is an exemplary case for policy transformation in the VMD. A hybrid governance paradigm that is characterised by the participatory and hierarchical approaches allows for the shared learning and interactions of knowledge vertically and horizontally among stakeholders. The study presents nuanced implications of the approach in incorporating both 'integrative' and 'adaptive' components into a long-term water governance strategy, which would serve as a two-pronged contribution to effectively manage environmental uncertainties facing the VMD. It also advocates for the legitimacy of the approach to be institutionalised and widely adopted across the Mekong floodplains and beyond.